2018
DOI: 10.1038/s41598-018-32835-y
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 32-mediated SOD1 aggregation is attenuated by pyrimidine-like compounds in living cells

Abstract: Over 160 mutations in superoxide dismutase 1 (SOD1) are associated with familial amyotrophic lateral sclerosis (fALS), where the main pathological feature is deposition of SOD1 into proteinaceous cytoplasmic inclusions. We previously showed that the tryptophan residue at position 32 (W32) mediates the prion-like propagation of SOD1 misfolding in cells, and that a W32S substitution blocks this phenomenon. Here, we used in vitro protein assays to demonstrate that a W32S substitution in SOD1-fALS mutants signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 59 publications
6
83
0
Order By: Relevance
“…Indeed, only a few simian species and the African elephant are known to incorporate tryptophan at this position while a conservative phenylalanine substitution is found at the equivalent position in human extracellular CuZnSOD (SOD3) indicating hydrophobicity at this site has some functionality. Accordingly, Pokrishevsky et al (2018) showed that substitution of Trp32 for the more frequently found serine decreases mutant and wild-type SOD1 stability and resistance to proteolytic digestion.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Indeed, only a few simian species and the African elephant are known to incorporate tryptophan at this position while a conservative phenylalanine substitution is found at the equivalent position in human extracellular CuZnSOD (SOD3) indicating hydrophobicity at this site has some functionality. Accordingly, Pokrishevsky et al (2018) showed that substitution of Trp32 for the more frequently found serine decreases mutant and wild-type SOD1 stability and resistance to proteolytic digestion.…”
Section: Small Moleculesmentioning
confidence: 99%
“…Modulation of ALS mutant SOD1 aggregation by substitution of Cys 111 to Ser has also been described [70][71][72]. The mutation of Trp 32 to Ser potently inhibited the ability of misfolded WT SOD1 to propagate between cells in culture [57,68,69]. Small molecules that bind near Trp 32 can block the seeding of mutant SOD1 aggregation in cell culture models [68,69,73].…”
Section: Introductionmentioning
confidence: 96%
“…Prior studies of ALS mutant SOD1 aggregation have shown that mutation of the unique Trp residue at position 32 of SOD1 to Ser or Phe can act in cis to suppress aggregation [38,[67][68][69]. Modulation of ALS mutant SOD1 aggregation by substitution of Cys 111 to Ser has also been described [70][71][72].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have found that the prion-like seeding and propagation of human wild-type SOD1 misfolding requires a tryptophan-tryptophan interaction in neighboring SOD1 molecules mediated by the single tryptophan at position 32 in SOD1 (Trp32) (10)(11)(12). Also, Trp32 mediates SOD1 aggregation in cultured cells, as well as zebrafish axonopathy in vivo (13,14). Furthermore, drugs that interact with Trp32 (15,16) can block propagated SOD1 aggregation in cell cultures and its toxicity in vivo (13,14).…”
Section: Introductionmentioning
confidence: 99%